2015
DOI: 10.3748/wjg.v21.i10.2973
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal esophagojejunostomy using the double stapling technique after laparoscopic total gastrectomy: A retrospective case-series study

Abstract: AIM:To introduce a simple and safe anvil insertion technique to esophagus during laparoscopic total gastrectomy (LTG). METHODS:Between July 2010 and December 2012, 58 consecutive patients with early gastric cancer underwent LTG were enrolled. We performed a simple and safe Roux-en-Y esophagojejunostomy using the double stapling technique to all patients. Then patients' characteristics, perioperative outcome and histopathologic data were analyzed retrospectively. RESULTS:The mean age and body mass index were 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…[ 35 36 ] We also collected several studies reported IEJ techniques in large scales and summarized them in Table 4 . [ 37 38 39 40 41 42 43 44 45 ] The surgical outcomes including operation time, blood loss, bowel recovery, and LOH were in accordance with the study.…”
Section: Discussionsupporting
confidence: 65%
“…[ 35 36 ] We also collected several studies reported IEJ techniques in large scales and summarized them in Table 4 . [ 37 38 39 40 41 42 43 44 45 ] The surgical outcomes including operation time, blood loss, bowel recovery, and LOH were in accordance with the study.…”
Section: Discussionsupporting
confidence: 65%
“…The type of stapler used for E‐J stomy has always been a controversial topic. Linear staplers and circular staplers perform comparably during LTG . Supporters of each stapler have their arguments and evidence, but there is no agreement according to our survey.…”
Section: Discussionmentioning
confidence: 59%
“…It is hard to explain why Chinese surgeons prefer a 60‐mm stapler, whereas Korean and Japanese surgeons use a 45‐mm stapler. With regard to a purse‐string suture with a 25‐mm circular stapler, both hand‐sewn and device‐assisted sutures have already been introduced, but their performance has rarely been compared in a prospective way .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of circular staplers presents additional challenges, including technical difficulties associated with the positioning of the stapler anvil. While systems of transoral anvil delivery have been developed, which can damage esophageal mucosa and can cause bacterial infections of the abdominal cavity [21].…”
Section: Discussionmentioning
confidence: 99%